2003
DOI: 10.11646/zootaxa.167.1.1
|View full text |Cite
|
Sign up to set email alerts
|

New species and records of Copris (Coleoptera: Scarabaeidae; Scarabaeinae) from Central America

Abstract: Two new species of Copris Geoffroy from Guatemala and Honduras are described and illustrated: Copris caliginosus sp. nov. and Copris nubilosus sp. nov. Both species are related to C. sallei Harold, which is redescribed and illustrated for the first time. A key for the remotus complex is also included. New distributional records of Copris are provided for five species and subspecies from Guatemala and El Salvador.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
0
9
0
2
Order By: Relevance
“…1996: 133 (parental care); Kohlmann et al . 2003: 47 (catalogue, distribution); Cabral-de-Mello et al . 2008: 1247 (chromosomal formula); Halffter et al .…”
Section: Copris Incertus Say 1835mentioning
confidence: 99%
See 1 more Smart Citation
“…1996: 133 (parental care); Kohlmann et al . 2003: 47 (catalogue, distribution); Cabral-de-Mello et al . 2008: 1247 (chromosomal formula); Halffter et al .…”
Section: Copris Incertus Say 1835mentioning
confidence: 99%
“…Since then, 11 additional New World species have been discovered and added to the genus (Matthews and Halffter 1968; Warner 1990; Ratcliffe 1998; Delgado and Kohlmann 2001; Kohlmann et al . 2003; Solís and Kohlmann 2003; McCleve and Kohlmann 2005; Mora-Aguilar and Delgado 2015). With the exception of Copris igualensis Warner, 1990 (of which only three specimens are known), the taxonomic organisation of the Copris incertus Say, 1835 species complex of the C .…”
Section: Introductionmentioning
confidence: 99%
“…Among the 20 species of dung beetle (Table 8), the presence of Copris laeviceps and Copris nubilosus suggests once again that Sierra Chinajá is an ecotone or area of transition, because these species are characteristic of two distinct biogeographic areas: the highlands of Alta Verapaz and the the lowlands of the Pe ten. Copris nubilosus was first described in 2003 (Kohlmann et al 2003) and until now was only reported from colder high-elevation cloud forests between 1350 and 1800 m, in the Sierra Cuchumatanes and Sierra de las Minas. Copris laeviceps is a characteristic lowland dung beetle recorded from sites in the Atlantic lowland forests of Izabal as well as the Pe ten Plateau to the north (Kohlmann et al 2003).…”
Section: Biogeographic Status Of Chinajámentioning
confidence: 99%
“…Copris nubilosus was first described in 2003 (Kohlmann et al 2003) and until now was only reported from colder high-elevation cloud forests between 1350 and 1800 m, in the Sierra Cuchumatanes and Sierra de las Minas. Copris laeviceps is a characteristic lowland dung beetle recorded from sites in the Atlantic lowland forests of Izabal as well as the Pe ten Plateau to the north (Kohlmann et al 2003).…”
Section: Biogeographic Status Of Chinajámentioning
confidence: 99%
“…2 in areas 5a [Sierra de las Minas] and 7b [La Union]). Evidence for a relationship between areas 7b-8 (La Union-Sierra de Merendon) and 3-5 (Cuchumatanes-Sierra de las Minas) includes the presence of the dung beetle, Copris nubilosus Kohlmann et al, from Cerro Azul (area 8; Copian, Honduras, 1,400 m), La Union, Zacapa, (area 7b), Purulh'a, Baja Verapaz (area 5a) and Barillas, Huehuetenango (area 3) (Kohlmann et al 2003). Also, species in the Petrejoides "reyesi" group, including P. reyesi Schuster (La Tigra, area 7d), P. pokomchii Schuster (Sierra de las Minas, area 5a), P. salvadorae Schuster (Trifinio, area 6), P. guatemalae Reyes-Castillo and Schuster (Cuchumatanes, area 3), and P. n. sp.…”
Section: Highland Biogeographic Scenariosmentioning
confidence: 99%